STANDAR PENGELOLAAN SEKOLAH DASAR ISLAM TERPADU DALAM KONTEKS PENDIDIKAN KARAKTER DI SDIT ADZKIA SUMATERA BARAT - Merri Yelliza; Novriandi; Hafizul; Herlina Saswita; Nurhayati; Irma Yendi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore how the management standards implemented at Adzkia Integrated Islamic Primary School (SDIT) West Sumatra contribute to the development of student character. The research used a descriptive qualitative approach through literature review and direct observation at SDIT Adzkia. The research subjects involved principals, teachers, administrative staff, students, and parents. Data were collected through interviews, observation, and document analysis. The results show that the implementation of Islamic value-based management standards involves curriculum management, human resources, finance, and relationships with parents. The implementation of these standards succeeded in improving students' discipline, responsibility, and empathy. However, some challenges such as limited resources and variability in staff commitment remain. In conclusion, Islamic value-based management standards can be an effective character education model if supported by close collaboration between schools and families and continuous training for educators. Recommendations are given to strengthen program evaluation and increase parental involvement in character education.